2013
DOI: 10.1002/macp.201300067
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Shell Thickness in Silica Nanospheres Functionalized by a Hydrophobic PMMA‐PSt Diblock Copolymer Brush via Activators Generated by Electron Transfer for Atom Transfer Radical Polymerization

Abstract: An improved strategy to synthesize SiO2‐PMMA nanoparticles with tunable shell thickness is demonstrated, via iron (III) catalyst‐mediated activators generated by electron transfer for atom transfer radical polymerization (AGET ATRP). To investigate the effect of the content monomer and ligand on the PMMA shell thickness, hydrophobic PMMA‐PSt diblock copolymer brushes on the surface of the silica nanospheres are designed and synthesized by AGET ATRP. Transmission electron microscopy (TEM) and field‐emission sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…This increased monomer scope has allowed researchers to prepare block copolymers using Fe-mediated RDRP. 71,77,84,85,88,101,102,111,136,142,153,154,159,161,164,165,167,173,179,183,184,198 These reports include amphiphilic A-PEO-A triblock copolymers (A = MMA or BMA prepared from polymerizations of the A monomer from a symmetrical bis(chloro)-terminated poly(ethylene oxide) macroinitiator (Figure 12a) 71 and block structures of multiple styrene derivatives. 164 Fe-mediated RDRP has also been used to prepare polymer brushes from designed macroinitiators including polyethylene-graftand polypropylene-graft-poly(methyl methacrylates) using peroxide modified PE and PP chains as initiators for chain growth (Figure 12b).…”
Section: Monomer and Macrostructure Scopementioning
confidence: 99%
See 1 more Smart Citation
“…This increased monomer scope has allowed researchers to prepare block copolymers using Fe-mediated RDRP. 71,77,84,85,88,101,102,111,136,142,153,154,159,161,164,165,167,173,179,183,184,198 These reports include amphiphilic A-PEO-A triblock copolymers (A = MMA or BMA prepared from polymerizations of the A monomer from a symmetrical bis(chloro)-terminated poly(ethylene oxide) macroinitiator (Figure 12a) 71 and block structures of multiple styrene derivatives. 164 Fe-mediated RDRP has also been used to prepare polymer brushes from designed macroinitiators including polyethylene-graftand polypropylene-graft-poly(methyl methacrylates) using peroxide modified PE and PP chains as initiators for chain growth (Figure 12b).…”
Section: Monomer and Macrostructure Scopementioning
confidence: 99%
“…Polymer scientists have used this strategy to prepare poly(acrylonitrile) decorated silica nanoparticles 189 and polystyrene resins, 188 as well as crosslinked networks 190 and ionic-liquid based microemulsions. 127 Similarly, ARGET ATRP conditions were used to modify silica nanoparticles 90,102 and poly(vinylidene fluoride) 92 by grafting PMMA chains onto their surfaces or chains. Little mechanistic study has been devoted to Fe-mediated ICAR, SARA and ARGET RDRP processes, with the assumption that the systems behave similarly to their copper counterparts.…”
Section: Reducing the Amount Of Fe Catalyst In Atrpmentioning
confidence: 99%
“…Elemental analyses indicated that 14.67 % and 9.67 % 4-amino-1,2,4-triazoles on FeL were grafted with PCA and RhB for FeL-PCA and FeL-RhB, respectively (Supporting Information, Table S1). Thermogravimetric (TG) analyses (Supporting Information, Figure S1) showed a mass loss of nearly 77.40 % for FeL at about 425 K, corresponding to the loss of 4-amino-1,2,4-triazoles, [10] whereas the mass losses of approximately 89.50 % and 87.70 % for FeL-PCA and FeL-RhB, respectively, at 1070 K were increased by 12.13 % and 10.34 % compared with FeL, which could be assigned to the removal of PCA and RhB on 4-amino-1,2,4-triazoles, [11] in accordance with the EA results. Powder X-ray diffraction (PXRD) studies revealed the intact The fluorescent emission spectra of FeL-PCA and FeL-RhB at room temperature are shown in Figure 1, where PCA, RhB, L-PCA, and L-RhB are also shown for comparison.…”
mentioning
confidence: 92%
“…A new adsorption peak in comparison with VS at 1530 cm −1 is the typical absorption peak of NH 2 present on the surface of VS‐NH 2 (Fig. 4, spectra b ) [23, 24]. The peaks at 2900, 1280 and 1380 cm −1 (Fig.…”
Section: Resultsmentioning
confidence: 97%